2016
DOI: 10.1039/c6en00088f
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of α-Fe2O3/polyacrylonitrile nanofiber mat as an effective lead adsorbent

Abstract: α-Fe2O3 nanoparticle has been widely used in water purification because of its effective adsorption performance. However, aggregation and difficulty in separation limit its practical application. Herein, we presented a polyacrylonitrile (PAN) nanofiber mat decorated with α-Fe2O3 as adsorbent for effective removal of Pb 2+ from contaminated water, which can solve the above problems easily. The α-Fe2O3/PAN nanofiber mats were prepared via electrospinning followed by a facile hydrothermal method and characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…The inorganic nanoparticles possessing ion-exchange properties are attractive to be used for heavy metal removal and the NF carriers can circumvent aggregation and increase their active sites. There have been reports on the incorporation of metal oxide nanoparticles [ 101 , 102 , 103 , 104 ], zeolite nanoparticles [ 105 ], and hydroxyapatite nanoparticles (Hap NP) [ 106 ] in polymer NF membranes by electrospinning for heavy metal adsorption. For example, Tran et al incorporated zeolite nanoparticles into electrospun cellulose acetate fibers to create free-standing IEX-NF membranes [ 107 ].…”
Section: Applications Of Nanofiber-based Iemsmentioning
confidence: 99%
“…The inorganic nanoparticles possessing ion-exchange properties are attractive to be used for heavy metal removal and the NF carriers can circumvent aggregation and increase their active sites. There have been reports on the incorporation of metal oxide nanoparticles [ 101 , 102 , 103 , 104 ], zeolite nanoparticles [ 105 ], and hydroxyapatite nanoparticles (Hap NP) [ 106 ] in polymer NF membranes by electrospinning for heavy metal adsorption. For example, Tran et al incorporated zeolite nanoparticles into electrospun cellulose acetate fibers to create free-standing IEX-NF membranes [ 107 ].…”
Section: Applications Of Nanofiber-based Iemsmentioning
confidence: 99%
“…Chang et al . studied poly(acrylonitrile) nanofibrous mats decorated with α‐Fe 2 O 3 as an effective lead adsorbent . It is suggested that the ion exchange between the Pb 2+ and protons of the hydroxyl bonded on the surface of the iron oxide accounted for the adsorption.…”
Section: Applications Of Ion‐exchange Nanofibersmentioning
confidence: 99%
“…Polyacrylonitrile (PAN)-based hybrid nanofibers are water insoluble and can be easily recovered from solution. Moreover, they have highly specific surface areas and functional nanoparticles; thus, these merits enhance their potential application [16,17]. In this work, we used a one-step method to prepare PAN/TiO 2 /Ag nanofibers (PAN/TiO 2 /Ag NF), and solvents such as N,N-dimethylformamide (DMF) served as electrospinning reducing agents for the synthesis of metallic Ag nanoparticles (AgNPs) [18].…”
Section: Introductionmentioning
confidence: 99%